CLOSE CIRCUIT CAMERAS’ (CCTV) SURVEILLANCE IN NEXUS WITH DATA PROTECTION LAWS, AND RIGHT OF PRIVACY IN PAKISTAN - Javed, Muhammad Waqas; Jamshed, Jibran; Bukhari, Syed Wajdan Rafay; Mahar, Shaza (The journal of contemporary issues in business and government, 2021)
The instant study is unique of its nature providing a comprehensive analysis on right of privacy and data protection laws in Pakistan with special reference to CCTV surveillance; its scope in the light of judgments of Apex or Higher Courts in Pakistan. It finds that right of privacy is interconnected with other fundamental right of life or right of dignity. CCTV surveillance in Pakistan is ever increasing and posing a threat to right of privacy; it deliberates the arguments about such surveillance in public or private domains and its legality. Further, it tries to intricate the existing legal framework in Pakistan either working as a mean of safeguard for privacy or a source of infringement for or against CCTV surveillance. Meanwhile, the study also presents critical analysis of the Proposed Data Protection Bill (PDPB), 2020 in the light of General Data Protection Regulations (GDPR), 2018.